Reasons for Undergoing CT During Childhood: Can CT-Exposed and CT-Naive Populations Be Compared?. Issue 1 (14th February 2020) - Shibata, Shunsuke; Shibamoto, Yuta; Maehara, Megumi; Hobo, Ayano; Hotta, Naohide; Ozawa, Yoshiyuki
Several epidemiological studies suggested an increased risk of cancer and other tumors in individuals undergoing computed tomography (CT) examination during childhood; however, it was questioned whether the group undergoing CT was comparable to that not undergoing CT. To address this issue, we investigated the reasons for undergoing CT in 763 children aged 0 to 19 years in 2013. Their medical records were fully evaluated and symptoms, underlying conditions, reasons for CT, and clinical courses after CT were investigated. Among the 763 children, 66.1% underwent repeat CT after the first examination, and 19.3% underwent CT 8 times or more. Among all the examined children, 8.8% had cancer and 4.7% had cancer-prone conditions such as Down syndrome, tuberous sclerosis, and cirrhosis. Only 11.4% of the 763 children underwent CT because of trauma, and 32.2% of the children had some types of congenital anomaly. The rate of trauma decreased with an increase in the frequency of CT examinations. Since the incidence of congenital anomalies is below 2.5% in the general population, it was concluded that the population of children undergoing CT is completely different from that not undergoing CT. The 2 groups should not be compared.